Examining Mate Similarity for Chronic and Non-chronic Criminal Behavior - van de Weijer, Steve G. A. (Journal of developmental and life-course criminology, 2022)
A growing amount of research suggests that members of a mating couple tend to be similar to each other across a range of phenotypes. Mating couples, for instance, often evince similar levels of antisocial, violent, and aggressive behaviors. Whether this type of similarity extends across measures of chronic and non-chronic forms of criminality has been considerably less scrutinized. This study examines whether persistent offenders seek out mates who engage in higher levels of offending. All 180,379 officially registered couples of which both partners were born in the Netherlands between 1984 and 1990 were included in the sample. Data drawn from the Dutch Police were used to examine suspected criminal behavior between the ages of 12 and 30 years old. Individuals belonging to certain offender groups were more likely to select partners from that same group. Moreover, the timing, frequency, and nature of criminal behavior of couples correlated positively. Results further revealed support for both assortative mating and behavioral contagion as explanations for mate similarity in criminality. We discuss the implications of our work for the study of intergenerational and life-course study of criminal behavior.